2010
DOI: 10.1007/s00011-010-0179-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and vascular changes in a rat monoarthritis model: prophylactic and therapeutic effects of meloxicam

Abstract: The present study provides a unique comparison of prophylactic versus therapeutic effects of meloxicam in the CFA-induced model of monoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
(70 reference statements)
2
7
0
Order By: Relevance
“…Our results confirmed that the complete Freund adjuvant model reproduced allodynia and hyperalgesia, as commonly described in patients (28). Pain behavior was dose-dependently reduced by meloxicam as previously shown in inflammatory pain models (21,(29)(30). Signs of inflammation were evidenced as paw circumference (i.e., edema) increase in Moars from day 3 to day 28.…”
Section: Discussionsupporting
confidence: 90%
“…Our results confirmed that the complete Freund adjuvant model reproduced allodynia and hyperalgesia, as commonly described in patients (28). Pain behavior was dose-dependently reduced by meloxicam as previously shown in inflammatory pain models (21,(29)(30). Signs of inflammation were evidenced as paw circumference (i.e., edema) increase in Moars from day 3 to day 28.…”
Section: Discussionsupporting
confidence: 90%
“…However, the formation of granulation tissue within the synovial subintimal region resulted in hypertrophic synovial tissue expanded to affect several other joints in the ankle. In this study and a previous study [ 30 ], we used a CFA volume of 20 μL to induce TTJ monoarthritis, which is a smaller volume, compared to many other studies [ 40 , 63 66 ]. Even with a volume of 20 μl, unintended massive inflammation affected surrounding tissue in the ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, joint immobilization leads to not only contracture, but also joint inflammatory conditions characterized by synovitis [13] and an upregulation of inflammation-related genes [14]. In addition, arthritis-induced contracture is partially prevented and improved by anti-inflammatory drugs [1517]. As such, anti-inflammatory treatment may prevent immobilization-induced contracture as well as arthritis-induced contracture.…”
Section: Introductionmentioning
confidence: 99%